Application of nuclear magnetic resonance for analyzing metabolic characteristics of winter diatom blooms. (20th December 2019) - Jeong, Kwang-Seuk; Jeong, Keon-Young; Hong, Young-ShiCk; Kim, Dong-Kyun; Oh, Hye-Ji; Chang, Kwang-Hyeon
Abstract: We compared two metabolome profiles of a small centric diatom species, Stephanodiscus hantzschii Grun., grown under conditions with enriched nutrients but different temperatures. This species proliferates in eutrophic rivers during winter. We investigated the population dynamics and internal metabolite changes of Stephanodiscus by performing a simple culture experiment at different temperatures (5 and 15°C). We applied the 1 H nuclear magnetic resonance (NMR) technique to fully grown cells to obtain the metabolite profiles of S. hantzschii . Growth rates were significantly different at different temperature conditions (0.99 ± 0.11 day −1 at 15°C and 0.21 ± 0.12 day −1 at 5°C, n  = 10). Characterized metabolites included saturated and unsaturated fatty acids, AXP (including AMP, ADP and ATP), and UDP-glucose and UDP-galactose, all of which are important for energy metabolism. These metabolites were abundant within S. hantzschii cells grown at 15°C but were not prolific in those grown at 5°C. Furthermore, other 1 H NMR spectrum uncovered very little amounts of metabolites. Based on these observations of cell growth rate, although required nutrients were supplied, colder temperatures suppressed population growth through the deactivation of various internal metabolisms. Thus, winter proliferation of this species is opportunistic, implying that survival success led to dominance in freshwater ecosystems with neither resource competition nor grazing pressure.